The Role of Female Lecturers of IAIN Ponorogo in Family Care During The Covid-19 Pandemic Period - Muafiah, Evi; Susanto, Susanto; Sofiana, Neng Eri; Khasanah, Uswatul (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2023)
This article identified female lecturers’ double burden along with the Covid-19 outbreak. During the plague, many people lost their jobs. Several families hardly struggled to fulfill their daily needs eventually forcing numerous women to work for gaining additional incomes. To diminish the Covid-19 virus transmission, working persons were directed to complete their duties from home. Furthermore, a child’s learning that used to be implemented at a school should be moved to the home, which then impacted parents’ role in assisting their kids’ education. This study uses qualitative methods which are analyzed using role theory. Data collection techniques used were interviews, google forms and documentation. This study concludes that women play a role in accompanying and helping children study at home online. On the other hand, women are also required to help meet family needs by working and domestic tasks. This shows the addition of the dual role of women during the Covid-19 pandemic. This dual role can be used as a compromise solution in family problems, especially for female lecturers at IAIN Ponorogo. The experiences of these female lecturers are varied, but many of them already have an equitable distribution of public and domestic roles as well as childcare between husband and wife.